Income Taxation and Hours Worked in Different Types of Entrepreneurship - Ege Can; Frank M. Fossen (Institute of Labor Economics (IZA), 2023)
We investigate the effect of personal income tax (PIT) rates on the number of hours entrepreneurs work weekly. Using the rotating panel data from the Annual Social and Economic Supplement of the Current Population Survey from 2003 to 2019, we estimate instrumental variable regressions in first differences to exploit changes in the tax code for identification. We distinguish between self-employed owners of incorporated versus unincorporated businesses and examine their differential responses. The findings reveal that higher individual-specific marginal PIT rates increase the hours worked among entrepreneurs with incorporated businesses, which could be explained by the availability of tax avoidance strategies. Among unincorporated entrepreneurs, we find a significant response to PIT rates in hours worked only for those who work 50 or more hours per week.
Keywords: H24; H25; J22; J23; L26; 330; income taxes; entrepreneurship; self-employment; labor supply; incorporated; unincorporated